How to manage generations? An Approach based on the Quality of Work Life (2019)
The objectives of this research are to examine whether there are significant differences in the perception of quality of work life among employees of three generational cohorts (i.e., Baby Boomers, Generation Xers and Millennials) and to propose some strategies from HRM in order to manage these differences. We used survey data collected from 522 employees of the logistic sector in Colombia and conducted internal consistency analysis, correlation analyses and one-way ANOVA. Results of ANOVA indicate that variables of quality of work life significantly differ depending on the generational membership of the employees. For example, Millennials were found to be a more distinct cohort from Gen Xers and Baby Boomers in terms of their relationship between promotion and career. However, the results suggest that employees in the older generations are likely to be more dedicated to, engrossed in, and even vigorous at work. For future studies, we recommend discussing how the knowledge on each generation in the workplace can inform specific HRM practices, such as how to train each generation effectively or to encourage each generation to improve work performance. Copyright © 2019. Laura MARTÍNEZ-BUELVAS and Olga JARAMILLO-NARANJO.